Factors associated with patient payments exceeding National Health Insurance fees and out-of-pocket payments in Lao PDR - Kongmany Chaleunvong; Bounfeng Phoummalaysith; Bouaphat Phonvixay; Manithong Vonglokham; Vanphanom Sychareun; Jo Durham; Dirk Essink (Taylor & Francis Group, 2020)
Background Attaining universal health coverage is a target in the Sustainable Development Goals. In Lao PDR, to achieve universal health coverage, the government is implementing a national insurance scheme, initially targeting the informal sector. Objective The purpose was to assess: i) the percentage of NHI patients who paid above the scheduled amount, based on individual billing payment; and ii) the factors related to overpayment. Methods Descriptive cross-sectional study based on a structured questionnaire administered at health facilities in face-to-face interviews with 1,850 patients in six provinces. Results All 1,850 participants worked in the informal sector. Of these, 78.8% of respondents (77.9% of in-patients; 79.5% of out-patients) made co-payments or were exempted from. Factors associated with in-patients paying above the scheduled fee were living in the province and district (OR = 2.8; 95%CI 1.2 to 6.3); not having documents with them (OR = 21.2; 95%CI 5.6 to 80.3); or not having documents (OR: 7.8; 95% CI 2.1 to 28.6). Significant factors associated with additional costs for out-patients were level of facility used at the provincial hospital (OR:1.4; 95% CI 1.1 to 1.9); older age (OR = 2.2; 95%CI 1.5 to 3.1); living in the province and district (OR = 2.3; 95%CI 1.5 to 3.7); living more than 5 km from the facility (OR = 1.4; 95%CI 1.1 to 1.9); buying medicine or supplies outside of the health facility (OR: 5.6; 95% CI 3.1 to 10.2); not bringing documents (OR:9.1; 95% CI 6.1 to 13.5), not having the right documents (OR: 8.9; 95% CI 5.4 to 14.8). Conclusions A number of patients paid above scheduled fee rates, which may deter people from utilising services when needing them. There is a need for increased understanding of the benefits of the national insurance scheme among patients and healthcare staff.